2020
DOI: 10.1101/2020.06.04.135640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The unconventional cytoplasmic sensing mechanism for ethanol chemotaxis inBacillus subtilis

Abstract: 205 words; Importance: 121 words Main Text: 4732 23 2 Abstract 24Motile bacteria sense chemical gradients using chemoreceptors, which consist of 25 distinct sensing and signaling domains. The general model is that the sensing domain 26 binds the chemical and the signaling domain induces the tactic response. Here, we 27 investigated the unconventional sensing mechanism for ethanol taxis in Bacillus subtilis. 28 Ethanol and other short-chain alcohols are attractants for B. subtilis. Two 29 chemoreceptors, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…To demonstrate the application of PyLipID to small-molecule/fragment binding, we analyzed the interactions of ethanol with a bacterial chemoreceptor, McpB, for which ethanol is a known attractant. The analyses were carried out on previously conducted atomistic simulations (3 × 600 ns) of an McpB cytoplasmic homodimer with 165 ethanol molecules (0.316 M) included to reproduce experimental conditions 40 . As anticipated, ethanol molecules showed transient interactions with the receptor due to their small size and simple structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the application of PyLipID to small-molecule/fragment binding, we analyzed the interactions of ethanol with a bacterial chemoreceptor, McpB, for which ethanol is a known attractant. The analyses were carried out on previously conducted atomistic simulations (3 × 600 ns) of an McpB cytoplasmic homodimer with 165 ethanol molecules (0.316 M) included to reproduce experimental conditions 40 . As anticipated, ethanol molecules showed transient interactions with the receptor due to their small size and simple structure.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that these may facilitate conformational changes induced by ethanol binding to be transmitted to other parts of the receptor, thereby enabling the signaling response. To test the sensitivity of PyLipID to minor changes in protein sequence, we additionally analyzed atomistic simulations (3 × 600 ns) of McpB carrying the A431S mutation, which is known to considerably reduce taxis to alcohols 40 . While the 51 ethanol binding sites identified by PyLipID largely overlap with those on wild-type McpB, ethanol binding to the sidechain of residue 431 was no longer observed (SI Fig S16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D). McpC was previously found to sense amino acids and HemAT to sense oxygen and alcohols (23)(24)(25). Functional redundancy of chemoreceptors for sensing aromatic compounds is also observed in other bacteria (26).…”
Section: B Subtilis Senses Phenol As An Attractant At Low Concentrations and A Repellent At High Concentrationmentioning
confidence: 87%
“…subtilis (Tohidifar et al, 2020). However, ethanol as a chemotactic agent has not been studied in eukaryotic cells to the best of the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%